Multistep approach to control microbial fouling of historic building materials by aerial phototrophs. Issue 3 (16th March 2019) - Nowicka-Krawczyk, Paulina; Żelazna-Wieczorek, Joanna; Koziróg, Anna; Otlewska, Anna; Rajkowska, Katarzyna; Piotrowska, Małgorzata; Gutarowska, Beata; Brycki, Bogumił
Abstract: The scientific multistep approach described herein is a result of two years of research into a control method against microbial fouling and biodeterioration of historic building materials by phototrophs. A series of tests were conducted to select the best antifouling agent for eliminating 'green' coatings and protecting surfaces against biofouling. Of the seven active compounds, two with the best penetration abilities were subjected to a photosynthetic activity inhibition test using confocal microscopy. Of the two, a quaternary ammonium salt (QAC) – didecyldimethylammonium chloride (DDAC) – was found to be the most effective. Ten biocides containing QACs at different concentrations were then tested against 'green' coatings on wood, brick and plaster, with the best four being selected for further research in model conditions. As a result, biocides containing >14% (v v –1 ) DDAC were found to be successful antifouling agents for protecting historical materials against biodeterioration by phototrophs.